2023
DOI: 10.1001/jamanetworkopen.2023.48914
|View full text |Cite
|
Sign up to set email alerts
|

Residential Structural Racism and Prevalence of Chronic Health Conditions

Dinushika Mohottige,
Clemontina A. Davenport,
Nrupen Bhavsar
et al.

Abstract: ImportanceStudies elucidating determinants of residential neighborhood–level health inequities are needed.ObjectiveTo quantify associations of structural racism indicators with neighborhood prevalence of chronic kidney disease (CKD), diabetes, and hypertension.Design, Setting, and ParticipantsThis cross-sectional study used public data (2012-2018) and deidentified electronic health records (2017-2018) to describe the burden of structural racism and the prevalence of CKD, diabetes, and hypertension in 150 resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…37 Our findings are consistent with a recent cross-sectional analysis in North Carolina by Mohottige et al, which identified an increased burden of structural racism indicators associated with higher neighborhood prevalence of hypertension, including lower percentages of White individuals in the neighborhood, high poverty rates, and higher ADI. 38…”
Section: Discussionmentioning
confidence: 99%
“…37 Our findings are consistent with a recent cross-sectional analysis in North Carolina by Mohottige et al, which identified an increased burden of structural racism indicators associated with higher neighborhood prevalence of hypertension, including lower percentages of White individuals in the neighborhood, high poverty rates, and higher ADI. 38…”
Section: Discussionmentioning
confidence: 99%
“…Among the domains associated with increased risk of sepsis, Black people have a higher burden of comorbidities [38,39], and alcohol dependence is more common in Black and Hispanic people [40] compared to White people. Residential racial segregation has been long-standing in the US and remains prevalent [41], with greater social deprivation in minority-predominant communities, especially of Black and Hispanic people [42,43]. In addition to its broad association with increased risk of sepsis [10], community-level social deprivation has been shown to be associated with greater prevalence of chronic health conditions, including those associated with sepsis [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Residential racial segregation has been long-standing in the US and remains prevalent [41], with greater social deprivation in minority-predominant communities, especially of Black and Hispanic people [42,43]. In addition to its broad association with increased risk of sepsis [10], community-level social deprivation has been shown to be associated with greater prevalence of chronic health conditions, including those associated with sepsis [43,44]. Furthermore, Black people tend to reside more commonly in medically underserved areas [11], with neighborhoods with a high proportion of Black people having less access to primary care [45], and Black and Hispanic people have been increasingly facing barriers to timely medical care compared to White people [46].…”
Section: Discussionmentioning
confidence: 99%